DEVELOPING TOURISM BUSINESS PROGRAM OF SAHID MONTANA HOTEL MALANG - Erica Delia Santoso; Dimas Rahmatullah; Lavinia Angeline; Raynardi Raznan; Husni Mubaroq; Eileen Wong Han Lin (AIBPM Publisher, 2018)
Sahid Montana is a 3 star hotel that located in the central of Malang City. This hotel has its own uniqueness and strenght, not like another modern hotel this hotel still keep the traditional culture. Therefore Sahid Montana want to go international by making some tour packages in Malang City and surrounding like Batu City and tourist can visit some nature tourism (mountains, beach, etc.). Sahid Montana doesn’t has country selection beacause there are so many tourist from many countries come to Malang City and stay in this hotel. To make Sahid Montana go international, this hotel need to develop the tourism in Malang so they need to do some promotion strategy like making website, social media, and participate in some international event. To develop Malang tourism,Team 19 offer 2 tour packages like Adventure Day for more nature tour and Hidden Malang for many unique places in Malang. The are some risk that Sahid might get by offering this packages to tourist like hotel has to spend more money for the promotion, tourist who come to Malang City is not so much so it’s impossible to get many tourist customers, and maybe the weather that we don’t know if it suddenly change (rain will ruin our nature tour). The recomendation that we suggest is developing the promotion strategy and buiding customers loyalty for Sahid Montana so customers will come again to this hotel.